2015
DOI: 10.17843/rpmesp.2015.321.1570
|View full text |Cite
|
Sign up to set email alerts
|

Intervención educativa para el control del dengue en entornos familiares en una comunidad de Colombia

Abstract: RESUMENObjetivos. Evaluar la eficacia de una intervención educativa para inducir cambios en la conducta de eliminar los criaderos del vector del dengue en familias de una comuna del Municipio de Sincelejo en Colombia. Materiales y métodos. Se realizó un estudio de una intervención educativa tipo antes y después, con un solo grupo a 54 familias seleccionadas por conveniencia. Se aplicó un programa educativo diseñado con los resultados de un test de conocimiento, una entrevista semiestructurada, guía de observac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
8
1
5
Order By: Relevance
“…Intermediate outcomes were the number of positive containers with larvae and/or pupae by house [22, 23, 30], overall average of positive containers with larvae and/or pupae (C+/C) [22], percentage of water-filled containers positive for larvae and/or pupae [25, 33, 48], and catch basins positive for larvae and pupae [62]. The results from Espinoza-Gómez et al [22] stress that using an EI, preceded by intersectoral integration with the community, had a significantly stronger effect on reducing breeding sites for Aedes aegypti than did chemical spraying.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Intermediate outcomes were the number of positive containers with larvae and/or pupae by house [22, 23, 30], overall average of positive containers with larvae and/or pupae (C+/C) [22], percentage of water-filled containers positive for larvae and/or pupae [25, 33, 48], and catch basins positive for larvae and pupae [62]. The results from Espinoza-Gómez et al [22] stress that using an EI, preceded by intersectoral integration with the community, had a significantly stronger effect on reducing breeding sites for Aedes aegypti than did chemical spraying.…”
Section: Resultsmentioning
confidence: 99%
“…The results from Espinoza-Gómez et al [22] stress that using an EI, preceded by intersectoral integration with the community, had a significantly stronger effect on reducing breeding sites for Aedes aegypti than did chemical spraying. Escudero-Támara and Villareal-Amaris [23] found a reduction of the number of Aedes breeding sites after an EI. Raju et al [25] found a significant reduction in the percentage of primary positive containers for Aedes albopictus , from 33 to 5% for tires, and from 42 to 8% for drums, after communities were mobilized in the Aedes aegypti control program for source reduction in the peri-urban district.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations